Basic reproduction numbers of three strains of mouse hepatitis viruses in mice - Nakayama, Masataka; Kyuwa, Shigeru (Microbiology and immunology, 2022)
Mouse hepatitis virus (MHV) is a murine coronavirus and one of the most important pathogens in laboratory mice. Although various strains of MHV have been isolated, they are generally excreted in the feces and transmitted oronasally via aerosols and contaminated bedding. In this study, we attempted to determine the basic reproduction numbers (R0) of three strains of MHV to improve our understanding of MHV infections in mice. Five‐week‐old female C57BL/6J mice were inoculated intranasally with either the Y, NuU, or JHM variant strain of MHV and housed with two naïve mice. After 4 weeks, the presence or absence of anti‐MHV antibody in the mice was determined by ELISA. We also examined the distribution of MHV in the organs of Y, NuU, or JHM variant‐infected mice. Our data suggest that the transmissibility of MHV is correlated with viral growth in the gastrointestinal tract of infected mice. To the best of our knowledge, this is the first report to address the basic reproduction numbers among pathogens in laboratory animals.